Contents - Editor-in-Chief (Thai Journal of Rheumatology, 2025)
1. Cardiovascular Disease Prevalence and Risk in Rheumatoid Arthritis Patients: Insights from a Nationwide Thai Hospital Database Abstract Natipoom Ketsing, Chingching Foocharoen, Siraphop Suwannaroj, Ajanee Mahakkanukrauh 1 - 6 2. Geriatric Rheumatology Chanikarn Oonjittichai, Pichaya O-charoen 7 - 26 3. Vasculitis mimics caused by Pythium infection and literatures review Angkana Norasetthada 27 - 36 4. A Case Report of Adult Type 2 Familial Hemophagocytic Lymphohistiocytosis Supatta Chaiprasert, Phongpon Sumangin 37 – 54 5. Rheumatology Quiz Anawat Suesuwan 55 – 58